2015
DOI: 10.1016/j.yfrne.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine control of seasonal plasticity in the auditory and vocal systems of fish

Abstract: Seasonal changes in reproductive-related vocal behavior are widespread among fishes. This review highlights recent studies of the vocal plainfin midshipman fish, Porichthys notatus, a neuroethological model system used for the past two decades to explore neural and endocrine mechanisms of vocal-acoustic social behaviors shared with tetrapods. Integrative approaches combining behavior, neurophysiology, neuropharmacology, neuroanatomy, and gene expression methodologies have taken advantage of simple, stereotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 130 publications
(308 reference statements)
1
41
0
Order By: Relevance
“…The current study maps FoxP2 mRNA expression in the brain of the highly vocal plainfin midshipman (Porichthys notatus) that has been the subject of comprehensive mapping of the central vocal, auditory, and neuroendocrine systems that modulate vocal-acoustic behaviors [ Fig. 1; see reviews in Bass, 2014;Forlano et al, 2015;Feng and Bass, 2017]. Comparison of the brain expression pattern of FoxP2 in midshipman with findings in other teleosts, as well as in mice and birds, suggests a pattern of evolutionarily conserved FoxP2-expressing brain regions.…”
Section: Introductionmentioning
confidence: 84%
“…The current study maps FoxP2 mRNA expression in the brain of the highly vocal plainfin midshipman (Porichthys notatus) that has been the subject of comprehensive mapping of the central vocal, auditory, and neuroendocrine systems that modulate vocal-acoustic behaviors [ Fig. 1; see reviews in Bass, 2014;Forlano et al, 2015;Feng and Bass, 2017]. Comparison of the brain expression pattern of FoxP2 in midshipman with findings in other teleosts, as well as in mice and birds, suggests a pattern of evolutionarily conserved FoxP2-expressing brain regions.…”
Section: Introductionmentioning
confidence: 84%
“…5). Nesting type I males produce three types of acoustic signals that include agonistic grunts and growls and advertisement calls known as hums Forlano et al 2015). Reproductive type I males often produce trains of broadband, short-duration (50-200 ms) grunts (Fig.…”
Section: Reproductive State-dependent Changes In Auditory Saccular Sementioning
confidence: 99%
“…In addition, Coffin et al (2012) also observed in reproductive females that the increase in saccular hair cell density was concurrent with increases in overall magnitude of the evoked saccular potentials and decreases in auditory saccular thresholds (.i.e., increased auditory sensitivity). The above-mentioned mechanisms potentially responsible for the observed seasonal changes in saccular sensitivity have been proposed to be induced by estrogens and androgens acting via long term signaling pathways to upregulate BK channels and modulate hair cell proliferation and death to ultimately enhance the hearing sensitivity in this species (Coffin et al 2012;Forlano et al 2015Forlano et al , 2016. However, this steroid-mediated mechanism hypothesis remains to be tested.…”
Section: Potential Mechanisms For the Plasticity Of Saccular Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The onset latency of the threshold responses (3 – 5 ms) suggests that they reflect auditory nerve activity. Thus, loci for androgen action could be the hair cells in the auditory periphery (Forlano et al 2015), or neurons in the acoustic ganglion expressing androgen receptor (Perez et al 1996). Androgens contribute to feminization or have female-specific effects in other species and are the primary steroid produced in the Xenopus ovary (Lutz et al 2001).…”
Section: Discussionmentioning
confidence: 99%